PMR Students' Skills in Performing First Aid in Accidents at SMAN 1 Telaga - Fadel Limomoto; Pipin Yunus; Susanti Monoarfa; Indrawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
First aid is the initial action given to victims of accidents or emergencies to prevent worsening conditions before receiving further medical treatment. Members of the Youth Red Cross (PMR) act as the frontline in the school environment, providing rapid and appropriate treatment when an incident requires an emergency response. The purpose of this study was to determine the level of knowledge and attitudes of PMR students regarding first aid. This study used a descriptive method with a total sampling of 34 respondents. Data collection was conducted using a questionnaire. The results showed that the level of knowledge of PMR students was categorized as good (23 respondents (67.6%)), fair (8 respondents (23.5%)), and poor (3 respondents (8.8%)). The attitudes of most students were categorized as high (24 respondents (70.6%)), moderate (7 respondents (20.6%)), and low (3 respondents (8.8%)). In conclusion, most PMR members have good knowledge and strong attitudes regarding first aid.